The Effect of Problem-Based Learning on Scientific Argumentation Skills in the Merdeka Belajar Curriculum - Wiwik Kartika Sari; Nidaul Hasanah; Ella Izzatin Nada (Universitas Sebelas Maret, 2025)
PBL encourages students to think openly, actively, and reflectively, which are essential components of critical thinking. This skill is significant for communication, collaboration, and problem-solving, all of which are integral to scientific argumentation. This study aims to determine the effect of problem-based learning models on students' scientific argumentation skills on the implementation of the Merdeka Belajar curriculum. This study used a non-equivalent pretest-posttest control group design. The sample was determined through cluster random sampling, and 2 classes were selected as control and experiment classes, with 32 students each. Data collection was carried out using scientific argumentation questions that had been declared valid by experts. The results reveal a significant improvement in the scientific argumentation skills of students in the experiment class that was taught using the Problem-Based Learning (PBL) model. The comparison between pre-test and post-test scores in both the experimental and control classes indicates that the Problem-Based Learning (PBL) model has a more pronounced effect in fostering students’ scientific argumentation skills than the inquiry-based model. While the control group exhibited some growth, the magnitude of change in the experimental group was noticeably greater. This suggests that the PBL approach not only helps students understand scientific content but also actively enhances their ability to articulate, justify, and critique scientific ideas.